1982
DOI: 10.7589/0090-3558-18.1.63
|View full text |Cite
|
Sign up to set email alerts
|

NASAL MITES (ACARI:HALARACHNIDAE) IN THE SPOTTED SEAL, Phoca largha PALLAS, AND OTHER PINNIPEDS OF ALASKAN WATERS

Abstract: The nasal passages of 349 pinnipeds of seven species were examined for halarachnid mites. Each of seven Steller sea lions (Eumetopias jubatus), 75 of 99 harbor seals (Phoca vitulina), and four of 71 spotted seals (P. largha) were infected, but none of 28 walruses (Odobenus rosmarus), 43 ringed seals (Phoca hispida), 58 ribbon seals (P. fasciata), and 43 bearded seals (Erignathus barbatus) was infected. The sea lions harbored Orthohalarachne attenuata (Banks, 1910) and O. diminuata (Doetschman, 1944), and the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1
1

Year Published

1987
1987
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 0 publications
2
24
1
1
Order By: Relevance
“…Nasal mites have only been reported once in wild walrus in 1947 (Newell 1947). A study surveying the frequency of occurrence of nasal mites in Alaskan pinnipeds did not find any mites in the 28 walrus examined, but did find mites in harbour seals ( Phoca vitulina ), spotted seals ( Phoca largha ) and Steller sea lion ( Eumetopias jubatus ) (Fay and others 1982). The Orthohalarachne mites caused nasopharyngeal inflammation in Steller sea lions, but the Halarachne mites found in the seals did not appear to cause inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nasal mites have only been reported once in wild walrus in 1947 (Newell 1947). A study surveying the frequency of occurrence of nasal mites in Alaskan pinnipeds did not find any mites in the 28 walrus examined, but did find mites in harbour seals ( Phoca vitulina ), spotted seals ( Phoca largha ) and Steller sea lion ( Eumetopias jubatus ) (Fay and others 1982). The Orthohalarachne mites caused nasopharyngeal inflammation in Steller sea lions, but the Halarachne mites found in the seals did not appear to cause inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The walruses in this case were diagnosed with nasal mites ( Orthohalarachne attenuata ). Nasal mites have only been reported in wild walrus in 1947 and, to the authors’ knowledge, have not been reported in wild walrus again (Newell 1947, Fay and others 1982). This report describes successful treatment of nasal mites in walrus using orally administered ivermectin with no adverse effects.…”
Section: Introductionmentioning
confidence: 91%
“…Adult Halarachne have been commonly described in the nasopharyngeal and lung mucosa, while the larvae are found mainly in the nasal passages (turbinates), feeding on the mucosa (Fay and Furman, 1982). The life cycle includes a free-living hexapod, followed by octopod protonymph and deutonymph, and eventually by the adult.…”
Section: Discussionmentioning
confidence: 99%
“…Intensity of infection was specified by means of a semiquantitative methodology: (-) no parasites observed, (+) a few to moderate (1-20) number of mites; (++) intense number of mites (>20). This range was established according to Fay and Furman (1982), as they considered heavier infestation than 20 mites did appear to be sufficient to cause significant irritation. When possible, the parasites were collected and stored in alcohol 70% for further identification.…”
Section: Methodsmentioning
confidence: 99%
“…Dos géneros de esta familia, Orthohalarachne y Halarachne Allman, 1847, son parásitos obligados de mamíferos pinnípedos. Las especies del genero Orthohalarachne parasitan a pinnípedos de las familias Otariidae Gray, 1825 y Odobenidae Allen, 1880 (Fay & Furman 1982). Orthohalarachne attenuata ha sido registrado parasitando el tracto respiratorio del oso marino ártico (Callorhinus ursinus Linnaeus, 1758), el lobo marino del Cabo (Arctocephalus pusillus Schreber, 1775), el león marino australiano (N. cinerea), el león marino de California (Z. californianus), morsa (Odobenus rosmarus Linnaeus, Figura 2.…”
Section: Descripciónunclassified